RESPONS FILIPINA TERHADAP PEMBANGUNAN PULAU BUATAN TIONGKOK DI WILAYAH LAUT TIONGKOK SELATAN (2022-2024) - Arasy, Wisnu Nur 'Alam; Takwa, Tuah Kalti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
This research examines the impact of China's construction of artificial islands in the South China Sea region on diplomatic relations between China and the Philippines in the period 2022-2024. The reclamation project and the construction of military infrastructure in the area claimed by China have created geopolitical tensions, especially with countries that geographically and legally have legitimate claims under UNCLOS, such as the Philippines. These tensions have a direct impact on the dynamics of bilateral relations, especially in terms of security cooperation and regional political stability. This research uses a qualitative approach with a case study method, and data collection techniques through literature study. In analysing the problem, this research utilises the theory of offensive realism as one of the main theories in the Neorealism perspective to understand the motives of China's power expansion, and the response of the Philippines as one of the consequences of said expansion. The analysis shows that the construction of artificial islands has worsened Philippine-China diplomatic relations. While economic cooperation continues, political and defence aspects are experiencing increased friction, including through the strengthening of trilateral relations between the Philippines, the United States and Japan. This research provides an understanding that unilateral development of disputed territories can create regional instability and encourage changes in the foreign policy strategies of affected countries. Keywords: South China Sea, diplomacy, artificial islands, military activity, foreign policy